Management of Public Information Services (Case Study PPID Soppeng District) - Syahrianti Syam; Muliana Umar; rosniar rosniar; Nur Arni Junianti (State Islamic Institute of Bone, Indonesia, 2022)
This research discusses the management of public information services in the Soppeng Regency area which is a study of the Soppeng Regency PPID as a form of good management of public bodies, which can later create an informative society. This study aims to identify the forms of management of public information services in Soppeng Regency and to analyze the role of PPID in Soppeng Regency in realizing public information disclosure. The method used is descriptive with a qualitative research approach. The determination of informants was carried out purposively, based on a homogeneous sample category that focused on one particular subgroup where all members of the sample were similar, such as a certain job or level in the organizational hierarchy. Namely consisting of the Head of Public Relations Management of Information and Documentation, Sub-coordinator of Public Information Services and Media Relations, Soppeng Regency Diskominfo staff, Partnership Facilitator and NOC Data Center Operator (Network Operation Center). Data collection is done by conducting interviews, documentation, and observation. Data analysis techniques are carried out by means of data reduction, data presentation, and drawing conclusions and verification. The results of the study show that the management of public information services in Soppeng Regency consists of data collection in the form of an information gathering process, an inventory of public information, whether self-produced, developed, received from other public bodies, or sent. The second is the preparation and provision of data, this section consists of two types, namely online data (available on the PPID website) and offline data stored at the PPID service center. The third is the classification of data which is divided into four types of data classification, namely information that is announced periodically, immediately, at any time, and information that is excluded. The role of the Soppeng Regency PPID in realizing public information openness, namely giving birth to changes in the culture of human resources in conventional community services to digital-based through websites, service displays, online service forms and information services through social media with the aim of creating faster and easier information services. realizing services that are smarter, and integrated with a system supported by information technology.